Effects of solid oxygen fertilizers and biochars on nitrous oxide production from agricultural soils in Florida - Tanumoy Bera (Nature Portfolio, 2020)
Abstract Elevated levels of nitrous oxide (N2O) emissions are a matter of concern in agricultural soils especially when flooding (hypoxic conditions) results from over irrigation or frequent rains. This study is the first to report the use of two solid oxygen fertilizers (SOFs, calcium peroxide and magnesium peroxide) to reduce N2O production in mineral and organic soils amended with N fertilizer in a short-term laboratory incubation besides two biochars. In general, organic soil had greater N2O production than mineral soil. Soils amended with nitrogen fertilizer exhibited increased N2O production, by 74 times in mineral soil and 2 times in organic soil. Both solid oxygen fertilizers in mineral soil (98–99%) and calcium peroxide in organic soil (25%) successfully reduced N2O production than corresponding N fertilized treatments. Additionally, a greater level of available nitrate–N (52–57 and 225 mg kg−1 in mineral and organic soil, respectively) was recorded with the solid oxygen fertilizers. Corn residue biochar with N fertilizer increased N2O production in mineral soil but decreased in organic soil, while pine bark biochar with N did not affect the N2O production in either soil. Depending on soil, appropriate SOFs applied were able to reduce N2O production and maintain greater nitrate–N levels in flooded soil. Thus, solid oxygen fertilizers can potentially be used as an effective way to reduce N2O emission from hypoxic soil in agricultural production systems.